2007
DOI: 10.1177/1098214007306372
|View full text |Cite
|
Sign up to set email alerts
|

Photolanguage

Abstract: This section includes shorter papers (e.g., 10-15 double-spaced manuscript pages or less) describing methods and techniques that can improve evaluation practice. Method notes may include reports of new evaluation tools, products, and/or services that are useful for practicing evaluators. Alternatively, they may describe new uses of existing tools. Also appropriate for this section are user-friendly guidelines for the proper use of conventional tools and methods, particularly for those that are commonly misused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Since then, researchers have utilized this method with a variety of populations including adolescents with cognitive challenges, students, low-literacy populations, and general adults (see a review by Bessell et al). Researchers have used this method in diverse cultural settings such as Australia, the Philippines, the United States, and so forth (Akeret, 2001;Bessell et al). Recently, the photolanguage process has been used as a tool for programmatic evaluations (Bessell et al;White, Sasser, Bogren, & Morgan, 2009) Although black-and-white images are mostly used in clinical psychology and program evaluations, color images are widely used in marketing (Hofstede, Hoof, Walenberg, & Jong, 2007) and health communication research (Houts, Doak, Doak, & Loscalzo, 2006).…”
Section: A Brief History Of Projective Techniques Photolanguage Andmentioning
confidence: 99%
See 4 more Smart Citations
“…Since then, researchers have utilized this method with a variety of populations including adolescents with cognitive challenges, students, low-literacy populations, and general adults (see a review by Bessell et al). Researchers have used this method in diverse cultural settings such as Australia, the Philippines, the United States, and so forth (Akeret, 2001;Bessell et al). Recently, the photolanguage process has been used as a tool for programmatic evaluations (Bessell et al;White, Sasser, Bogren, & Morgan, 2009) Although black-and-white images are mostly used in clinical psychology and program evaluations, color images are widely used in marketing (Hofstede, Hoof, Walenberg, & Jong, 2007) and health communication research (Houts, Doak, Doak, & Loscalzo, 2006).…”
Section: A Brief History Of Projective Techniques Photolanguage Andmentioning
confidence: 99%
“…Researchers have used this method in diverse cultural settings such as Australia, the Philippines, the United States, and so forth (Akeret, 2001;Bessell et al). Recently, the photolanguage process has been used as a tool for programmatic evaluations (Bessell et al;White, Sasser, Bogren, & Morgan, 2009) Although black-and-white images are mostly used in clinical psychology and program evaluations, color images are widely used in marketing (Hofstede, Hoof, Walenberg, & Jong, 2007) and health communication research (Houts, Doak, Doak, & Loscalzo, 2006). Educational researchers have found that color photographs facilitate viewers' comprehension (Readence & Moore, 1981).…”
Section: A Brief History Of Projective Techniques Photolanguage Andmentioning
confidence: 99%
See 3 more Smart Citations